WHAT MAKES EXPERIENCE A MEMORABLE ONE FOR THE CUSTOMERS OF TOP INDONESIAN HOTELS - Herjanto, Halimin; S. Gaur, Sanjaya (ITB Journal Publisher, LPPM ITB, 2014)
With the increased competition within the Indonesian hotel industry, the need forhoteliers to create memorable hotel experiences for customers is becoming increasingly important. A better understanding of how to create such experiences can help ensure customers revisit a hotel and maintain their sense of loyalty. This study analyses and discusses real hotel customers’ reviews and feedback about their stay in the Top 10 Hotels in Indonesia. The findings show that perceptions of hospitality, perceptions of space and the overall hotel experience are the three most important factors in creating a memorable experience for Indonesian hotel customers. Limitations of this study and the avenues for future study are also discussed.